(untitled) (Contemporary Journal of Social Science Review, 2025)
The purpose of this study is to look into the connection between bullying at work and workers’ productivity. Employee bullying will be assessed using the NAQ-R:(Tambur & Vadi, 2009) with differences between Work related- and person-related bullying. To fulfill the study’s goals, information was gathered from workers in the banking sector. The results of the reliability test for work related bullying, person related bulling and employee productivity is respectively. Bullying at work has a negative with work performance, according to the data analysis done with SPSS (version-21) and the productivity was the outcome. Linear regression analysis revealed that factors like bullying that is tied to an individual has an impact on work productivity. The study also discovered that bullying-related factors were anticipated to have a significant impact on job performance. Linear regression analysis was used to create a predictor model. A number of suggestions were made to managers, executives, and the industrial sector regarding additional initiatives that could be implemented to create a high-quality workplace where workers could perform well. Future research objectives, constraints, and theoretical and practical implications are also highlighted in this study.